PERPADUAN JAWA-EROPA KEARTISTIKAN INTERIOR DALEM WURYANINGRATAN - Budiwiyanto, Joko (Institut Seni Indoensia Surakarta, 2009)
This article is a part of research result about Architecture Profile of Princeâ€™s fashion: â€œThe Artistic Value of Interior of Dalem Wuryaningratan of Kasunanan Palace Surakartaâ€. The research objective is to reveal the artistic value of interior of Dalem Wuryaningratan. The research result shows that in the matter of the artistic of its interior design, dalem pangeran always oriented toward symbolic classification based on two, four, and eight. The view of classification two always manifested with kiwa-tengen, atas-bawah, or loroning-atunggal is always combined with something bigger and absolute. The view is not contrast; it is a relationship between two different things but it is harmonious. The balance controller is a point in the middle (the third point) which is absolute or God. Symmetric conception in interior element design shows the meaning of harmony. The conception is a manifestation from the meaning of balance with a purpose to reach the harmony of live, which means living harmoniously each other, living harmoniously with nature, and living harmoniously with God. The dualism conception is reflected in the room structure, door, window and colonnade/saka arrangement, and even in the structuring of furniture.